Studi terhadap Pengukuran Kinerja Akuntansi Perusahaan Prospektor dan Defender, dan Hubungannya dengan Harga Saham : Analisis dengan Pendekatan Life Cycle Theory - Abd Hamid Habbe; Jogiyanto Hartono (The Indonesian Journal of Accounting Research, 2013)
The objective of the study is to empirically examine the difference from accounting performance measures that implicated by prospector and defender strategies, and to examine the differences between market reactions to both organizational strategies. Variables that implicated by organizational strategy are income growth, sales growth, and dividend pay out. Life cycle theory is used to analyze the difference from accounting performance measures.Four variables are used to determine prospector and defender firms: the price-to- book value ratio, the ratio of employees to sales, the ratio of capital expenditure to market value of equity, and the ratio of capital expenditure to total asset. These variables are analyzed by common factor analysis. Based on the common factor analysis, 25 prospector and 25 defender firms are derived from 74 manufacturing public firms at Jakarta Stock Exchange.The empirical results show that income and sales growth of prospector firms are greater than that of defender firms (significant at 0.01 level). Dividend pay out and market reaction, however, are not significantly difference between prospector and defender firms. Multivariate test was employed to understand more the differences between prospector and defender firms in relation to the stock prices.  The results show that the magnitude of income and sales growth of prospector firms significantly affects the magnitude of abnormal return (significant at 0.05 and 0.10 level, respectively). While, at defender firms, only the magnitude of income growth significantly affects the magnitude of abnormal return. Dividend pay out does not affect the magnitude of abnormal return for both prospector and defender firms. However, the effects of the magnitude income and sales growth to the magnitude of abnormal return between prospector and defender firms are not significantly difference.